Angļu valodas vārdu krājuma paplašināšana un mijkultūru izglītība vidusskolā - Maļjuhina, Alla (Latvijas Universitāte, 2008)
Diplomdarba tēma ir ,,Angļu valodas vārdu krājuma paplašināšana un mijkultūru izglītība vidusskolā.’’ Diplomdarbs ,,Angļu valodas vārdu krājuma paplašināšana un mijkultūru izglītība vidusskolā” veltīts ļoti svarīgam angļu valodas kā svešvalodas mācīšanas aspektam. Tas apskata izglītojamo vārdu krājuma paplašināšanas un mijkultūru daudzveidības iespējas, visefektīvāko metožu izmantošana, stratēģijas un tehnikas, modernas informatīvas tehnoloģijas. Pētījumā analizēta teorētiska literatūra par vārdu krājuma paplašināšanu un mijkultūru daudzveidības iespējas, kā arī veikts case study. Diplomdarba autore secina, ka, ja angļu valodas stundās tiek izmantoti uzdevumi ir izstrādāti saskaņā ar mijkultūru izglītības principiem, tie veicina skolēnu mijkultūru kompetences pilnveidi. Pētījums pierāda izvirzīto hipotēzi, ka vārdu krājuma paplašināšana mācīšana un mijkultūru daudzveidība efektīvāka, ja vārdu krājuma paplašināšana mācīšana un mijkultūru daudzveidība principi ievēroti; un skolotāja izmantoja daudzveidīgas metodes gan tradicionālo, gan netradicionālo metodiku angļu valodas stundās. Diplomdarbā gūtie rezultāti un secinājumi var tikt izmantoti angļu valodas stundās.

The diploma paper ‘’English Vocabulary Development and Intercultural Education at Secondary School’’ deals with English vocabulary development and intercultural education of learners by choosing the most efficient teaching and learning methods, strategies and techniques, modern information technologies. The aim of the present research is to investigate some of the most effective methods and techniques used for English vocabulary development and intercultural education in English Language Teaching (ELT). The methods of the research and data collection are the analysis of theoretical literature on English vocabulary development and intercultural education, the case study and analysis of the obtained data. The importance of English vocabulary development and intercultural education is stressed. English vocabulary development and fostering students’ intercultural communicative competence by means of different activities is shown. The description and analysis of the case study is presented. The author concluded that English vocabulary learning develops effectively if English vocabulary development and intercultural education principles are observed; and teacher uses a variety of methods of traditional and untraditional methodology. The results and conclusions of this research can be used at the English language lessons in order to make the English vocabulary development and intercultural education at secondary school process more effective.
English Vocabulary Development and Intercultural Education at Secondary School
Keywords: Pedagoģija